Physical gels from biological and synthetic polymers - Djabourov, Madeleine, 1949-; Nishinari, Katsuyoshi; Ross-Murphy, S. B. (Cambridge University Press, 2013)
Presenting a unique perspective on state-of-the-art physical gels, this interdisciplinary guide provides a complete, critical analysis of the field and highlights recent developments. It shows the interconnections between the key aspects of gels, from molecules and structure through to rheological and functional properties, with each chapter focusing on a different class of gel. There is also a final chapter covering innovative systems and applications, providing the information needed to understand current and future practical applications of gels in the pharmaceutical, agricultural, cosmetic, chemical and food industries. Many research teams are involved in the field of gels, including theoreticians, experimentalists and chemical engineers, but this interdisciplinary book collates and rationalises the many different points of view to provide a clear understanding of these complex systems for researchers and graduate students.
Keywords: Polymer colloids.; elektronické knihy; electronic books